Use of non-conventional woods in cocoa fermenters and their influence on the organoleptic quality of the cocoa paste (Revista Científica Interdisciplinaria Investigación y Saberes, 2022)
The research was carried out at the Quevedo State Technical University, Faculty of Livestock Sciences, located in the Experimental Farm "La María". The influence of cocoa fermenters made from woods (Guayacán Blanco, Laurel, Pine) on the physicochemical quality of Trinitario and Nacional variety cocoa beans was evaluated; sensory and bromatological analysis of the cocoa paste. A completely randomized design (DCA) with factorial arrangement (3x2) was applied, it was determined by the cut test the minimum 60% of well fermented almonds, violet beans 21%, slate beans exceeded 12%, as for the specific flavor profile it was determined that the T1 (C. Nacional-C. Laurel) Cacao odor, T6 (C. Trinitario-Pino) Floral profile, T2 (C. Trinitario-Guayacán Blanco) Sweet and presents the best attributes; as for the basic bitterness flavor profile, T3 (C. Nacional-Pino) has a high average; T6 and T5 (Nacional-Guayacán Blanco) obtain an average in acidity and astringency; in acquired flavors Green and Mold, T6 and T3 present high averages in the cocoa paste. Regarding the physical-chemical analysis, T6 shows moisture (2.44%), T5 (3.37%) in ash, (51.11%) in fat, T4 (Trinitario-Laurel), T6 with a pH of (5.82) and T5 shows an acidity of (1.34%) in the cocoa paste. The maximum temperature reached in the fermentation of the Nacional cocoa (44.52°C) in pinewood crates, while the minimum temperature was for the Trinitario cocoa (35.66°C) in the fermenter made of Guayacán Blanco wood.